Pengaruh Persepsi Pengurus Dewan Kemakmuran Masjid tentang Konsep Bagi Hasil terhadap Minat Menyimpan Dana di Bank Syariah - purnama Putra (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2017)
The purpose of this study is to determine the influence of the Board of Prosperity Board Mosque's perception of the concept of profit sharing on interest in depositing funds in sharia banks. From the results of research that has been done to the board members of the Board of Prosperity Mosque Mosque Jami 'Al-Azhar Bekasi get the result that the Board of Prosperity Mosque Jami Al Azhar Bekasi has a positive perception of the concept of profit sharing applied in Islamic banks. The board of the Prosperity Council of the Mosque gave an answer that the concept of profit sharing applied in Islamic banks based on the principle of justice and has been in accordance with Islamic Shari'a. The board of the Prosperity Council of the Mosque of Jami Al Azhar Bekasi is interested to keep his funds in sharia bank even has kept his funds in sharia bank. The data obtained from the results of research processed by using SPSS 17 with Test-t get the result that the influence between the perception Board of Moslem Moslem Council about the concept of profit sharing on interest in depositing funds in Islamic Banks is evidenced by the results of simple linear regression test to get significant results.